Blackout : a novel - Elsberg, Marc, 1967- (Sourcebooks Landmark, 2017)
When the lights go out one night, no one panics. Not yet. The lights always come back on soon, don't they? Surely it's a glitch, a storm, a malfunction. But something seems strange about this night. Across Europe, controllers watch in disbelief as electrical grids collapse. There is no power, anywhere. A former hacker and activist, Piero investigates a possible cause of the disaster. The authorities don't believe him, and he soon becomes a prime suspect himself. With the United States now also at risk, Piero goes on the run with Lauren Shannon, a young American CNN reporter based in Paris, desperate to uncover who is behind the attacks. After all, the power doesn't just keep the lights on--it keeps us alive.